NEGOTIATING ETHNIC IDENTITY - WHAT DOES IT MEAN TO BE A SERBIAN STUDENT AT THE UNIVERSITY OF VIENNA? - Vladan; Šljukić, Marica; Stojšin, Snežana (National interest, 2023)
This paper explores the strategies employed by Serbian students studying in Vienna in negotiating their ethnic identity. Negotiation strategies are defined as the processes through which individuals reconcile their internal understanding of ethnicity with external definitions. This involves examining the extent of alignment between these two perceptions and the mechanisms immigrants employ to bridge potential disparities. The study places particular emphasis on the interactions of Serbian students with the majority ethnic group in both informal and formal settings, contextualized within contemporary Austrian society. The research employs a mixed methods approach. In the initial phase, data collection was executed through an online focus group interview, involving the participation of six students with diverse socio-demographic characteristics. This preparatory phase laid the groundwork for the subsequent stage, which revolved around the development and deployment of an online questionnaire. The online questionnaire was completed by 287 students from various universities in Vienna, spanning different levels of study. Based on the collected data, the paper concludes that Serbian students in Vienna are faced with an external definition of ethnicity that does not match their internal one, and that they resolve this discrepancy through various mechanisms of adapting their own ethnic identity to the requirements of the new social context.